Effect of biofeedback – therapy on clinical semiology, quality of life and sensorimotor function of anorectal area at irritable bowel syndrome with refractory constipation - O. V. Krapivnaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate effect of biofeedback-therapy (BFT) on clinical symptoms, quality of life, sensorimotor function of anorectal area at irritable bowel syndrome (IBS) with refractory constipation (IBS-C).Material and methods. Overall 38 patients with IBS-C (according to Rome III criteria) were investigated. All patient underwent BFT (mean No of sessions 6,1±0,9) with rating of IBS symptoms, quality of life (by SF-36 questionnaire), parameters of anorectal manometry before the termination of BFT course.Results. According to anorectal manometry data 1-st type defecation dyssynergy (DD) was diagnosed in 28,9% of patients, dysfunction of an external anal sphincter – in 71,1%. BFT was effective in 24 (63%) patients: in 17 (62,9%) with IBS-C and in 7 (63,6%) with IBS-C and 1-st type DD. Frequency of defecations has increased from 1,1±0,1 to 4,9±0,3 per week (p<0,001), other IBS symptoms (p<0,01) have decreased. Defecation index (OR 6,5; 95% – CI 1,09–39,3) was significant prognostic factor for BFT efficacy.Conclusions. In 63% of patients with IBS-C BFT was effective. The high defecation index (> 1,2) is significant prognostic factor for BFT efficacy.